Potensi Daun Jambu Biji sebagai Agen Antiinflamasi untuk Perawatan Trauma Puting pada Ibu Menyusui: Literature Review - Husna, Dewi Asmaul; Wijayanti, Krisdiana; Susanto, Edy (Universitas Malahayati, 2025)
ABSTRACT Trauma to the nipple such as excoriation (abrasions), hyperemia, and fissures is often one of the main reasons mothers stop breastfeeding. Therefore, proper treatment is needed to prevent this condition. Research related to non-pharmacological therapy as an effort to treat nipple trauma has been conducted, one of which is by utilizing plants containing flavonoids that function as anti-inflammatory agents. This study aims to examine the potential of guava leaves as an anti-inflammatory agent that can be used as an alternative treatment for nipple trauma. This article adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as a guideline. The database was taken from Science Direct, PubMed, and Google Scholar. The search was conducted using keywords such as